Fomentar el desarrollo económico a través de la implementación de un centro de capacitación en asesoría contable financiera para el sector arrocero del recinto Boca de Caña del cantón Samborondón de la provincia del Guayas - López Mendoza, Johanna Anabelle (2015)
The current work of investigation was done in the fairground Boca de Caña , Tarifa located in the cantón Samborondón the information through poll and interview’s to the habitant’s of this place was a large contribution of development of this project . In the course of the investigation we found that the population in Boca De Caña they lack the orientation of market and stability, operation, implementation of their business could be damaging if they don’t have apply rules ,norms, by the law………